2004
DOI: 10.4314/bcse.v17i2.61675
|View full text |Cite
|
Sign up to set email alerts
|

<b>Bioactive metabolites from <i>Trichoderma harzianum</i> and <i>Trichoderma longibrachiatum</i></b>

Abstract: The tea plant, Camellia sinensis (L.) O. Kuntze is an important crop in the agriculturally based economy of Kenya. Many diseases affect the tea plant but the most prevalent is armillaria root rot caused by the fungus Armillaria mellea. Compounds from the fermentation of Trichoderma species in different media were bioassayed against some selected gram-positive and gram-negative bacteria, fungi including Armillaria mellea, a yeast and a Mucor. Compounds obtained from T. harzianum, and T. longibrachiatum when cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 11 publications
0
34
0
1
Order By: Relevance
“…lycopersici , Fusarium verticilioides (moniliforme ), Phytophthora megasperma , Rhizoctonia solani , and Armillaria mellea (Al- Heeti and Sinclair 1988;Scarselletti and Faull 1994;Worasatit et al 1994;Poole et al 1998;Tarus et al 2003). In addition, it has been shown that 6-n-pentyl-2H-pyran-2-one can reduce the production of deoxynivalenol by Fusarium graminearum on agar medium (Cooney et al 2001).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…lycopersici , Fusarium verticilioides (moniliforme ), Phytophthora megasperma , Rhizoctonia solani , and Armillaria mellea (Al- Heeti and Sinclair 1988;Scarselletti and Faull 1994;Worasatit et al 1994;Poole et al 1998;Tarus et al 2003). In addition, it has been shown that 6-n-pentyl-2H-pyran-2-one can reduce the production of deoxynivalenol by Fusarium graminearum on agar medium (Cooney et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…These volatiles have been described for T. atroviride , T. aureoviride , T. harzianum , T. longibrachiatum , T. pseudokoningii, and T. viride, and their spectrum is characteristic for each strain as well as dependent on growth phase and nutritional, biological, and environmental conditions (Wheatley et al 1997;Bruce et al 2000;Tarus et al 2003;Nemčovič et al 2008;Stoppacher et al 2010;Polizzi et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1-phenyl-3-methylpyrazolones oxidoreductase mediators [297] aryl tetral226in lignans bioactive compounds [298] podophyllotoxin bioactive compounds [298] Trametes versicolor funatrol D bioactive compound [299] isodrimenediol sesquiterpenes (anticancer) [299] tramspiroins sesquiterpenes (anticancer) [299] triterpenes bioactive compounds [300] Database on potential toxigenic capacities of microorganisms used for industrial production 2,4-di-tert-butylphenol bioactive compound [310] 2,6,10-trimethylundeca-5,9-dienal bioactive compound [310] 2-phenylethanol bioactive compound [311] 6-pentyl-alpha-pyrone bioactive compound [312,313] 6-methyl-1,3,8-trihydroxyanthraquinone antifungal [308] 6-n-pentyl-a-pyrone bioactive compound [311] 6-pentyl-2H-pyran-2-one antifungal [308] alpha-cubebene bioactive compound [310] alpha-curcumene bioactive compound [310] anthraquinones antifungal [314] azaphilone antifungal [307,309] b-bisabolene bioactive compound [310] biformen (6CI) bioactive compound [310] butenolide antifungal [307,309] [318] gliotoxin bioactive compound [319] gliovirin bioactive compound [319,320] harzianic acid siderophore [321] harzianolide anti-phytopathogen [307,309,322] harzianopyridone anti-phytopathogen [307][308][309] harziphilone bioactive compound [318] hexahydrofarnesol bioactive compound …”
Section: Trametes Hirsutamentioning
confidence: 99%
“…tandyukisins B-D (decalin derivative) cytotoxic [328] trichodenone A, B, C cytotoxic [329] trichodermin trichotecene toxin [319,330] trichodermol (detected in hydrolysed crude extracts) trichotecene toxin [331] trichorzin peptaibol [332] tyrosol bioactive compound [311] verticillol bioactive compound [310] viridiofungin A anti-phytopathogen [333] Trichoderma koningii 6, 4-oxopentyl-2H-pyran-2-one antifungal [334] 6-pentyl-pyranone antifungal [334] 7-O-methylkoninginin D (polyketide derivative) antimicrobial [335] alpha-aminoisobutyric acid [336] amino alcohol (peptaibols) [336] decanolactone antifungal [334] koninginins A, D, E, F, L, M phospholipase A 2 inhibitors [335,337,338] stigmasterol antifungal [334] trichodermaketones A-D (polyketide derivatives) antimicrobial [335,337] trichokonins (peptaibols) antimicrobial [339][340][341] Trichoderma longibranchiatum longibranchins (LGA I-V and LGB II-III) (peptaibols) biooactive compounds [342][343][344][345] Database on potential toxigenic capacities of microorganisms used for industrial production…”
Section: Microorganism Secondary Metabolites Commentsmentioning
confidence: 99%